Effects of Empowerment, Work Climate and Job Satisfaction on Employee Performance of Transportation Office of Klungkung Regency - Luh Kadek Budi Martini; A. A. Dwi Widyani (Universitas Warmadewa, 2019)
To achieve maximum work results and satisfy, empowerment is needed by an employee in carrying out their duties so that employee performance can be improved. In addition, the work climate also affects employee performance. An open organizational climate encourages employees to express their interests and dissatisfaction without fear of retaliation and attention. In addition to the work climate, job satisfaction also affects employee performance, job satisfaction as a pleasant or positive emotional state that arises results from research on a job. The sample under this study was 63 employees at the Transportation Office of Klungkung Regency. The determination of the sample used the slovin method. The method in this recent study is quantitave approach and the analytical instrument used was multiple linear regression analysis; multiple correlation, determination, t test and F test. The results showed that the empowerment variable had a positive effect on employee performance as indicated by the significance value of 0.026